2012
DOI: 10.2147/ijn.s34574
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of greater cardiomyocyte functions on conductive nanoengineered composites for cardiovascular application

Abstract: Background: Recent advances in nanotechnology (materials with at least one dimension between 1 nm and 100 nm) have led to the use of nanomaterials in numerous medical device applications. Recently, nanomaterials have been used to create innovative biomaterials for cardiovascular applications. Specifically, carbon nanofibers (CNF) embedded in poly(lacticco-glycolic-acid) (PLGA) have been shown to promote cardiomyocyte growth compared with conventional polymer substrates, but the mechanisms involved in such even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…These filamentous carbon nanomaterials (CNMs) possess excellent physical properties and, in comparison with GO, they have lower price and higher electrical conductivity [18]. Thus, CNFs can be utilized to fabricate conductive composites [19] for biomedical applications [20].…”
Section: Introductionmentioning
confidence: 99%
“…These filamentous carbon nanomaterials (CNMs) possess excellent physical properties and, in comparison with GO, they have lower price and higher electrical conductivity [18]. Thus, CNFs can be utilized to fabricate conductive composites [19] for biomedical applications [20].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these curved graphitic materials are nowadays employed in industrial fields such as polymer additives, gas storage materials, and catalyst supports [32]. Additionally, it has been demonstrated that composites with CNFs are able to promote cardiomyocyte growth [33] and neural regeneration [34] in biomedicine.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, we created synthetic substrates using a widely used polymer (PCL) 30 with a modulus similar to cardiac tissue 31, 32 (reported in our previous study 33 ). This polymer was spin-coated into a flat uniform sheet (as a control with morphology similar to TCPS) as well as electrospun into aligned/less aligned fibers to create structures similar to those found in the human heart.…”
Section: Discussionmentioning
confidence: 99%